The Effect of Green Innovation and Integrated Reporting on Company Performance with Company Size as a Moderating Variable - Afriyanti Afriyanti; Etty Murwaningsari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The objective of this study is to evaluate the extent to which the size of a corporation influences the outcomes of integrated reporting and environmentally conscious innovation. Despite the conflicting evidence, this study looks at the annual reports and sustainability reports of non-financial companies with the goal of determining whether or not they will list on the IDX in the years 2020–2021. The information utilized in this investigation was obtained from the website of the Indonesian Stock Exchange (IDX). According to some projections, there might be as many as 131 non-financial companies listed on the stock market in the year 2020, and this number could rise to as many as 238 in the year 2021. According to the findings, both environmentally responsible innovation and integrated reporting are factors that contribute to the expansion of the company. In addition, the findings point to a connection between the size of a company and both a weakening of the association between environmentally friendly innovations and successful business and a strengthening of the association between successful business and integrated reporting. Both of these associations are affected by the size of the company.